(untitled) (Medical Forum Monthly, 2024)
Objective: To asses culture and sensitivity of renal infection patients detected on ultrasound Study Design: Prospective cohort study Place and Duration of Study: This study was conducted at the Rimsha Medical Center Dadu from January 2012 to June 2015. Materials and Methods: Hundred patients suffering for renal infection detected on ultrasound were included in the study. Diabetic and urolithiasis patients excluded from the study. Urine culture and sensitivity of renal infection patients detected on ultrasound carried from collection point of diagnostic and research laboratory liaqaut university of medical & health sciences Jamshoro/Hyderabad in Dadu. Results: Out of 100 patients 65 (65%) were female and 35(35%) male. The age of the patients ranged from 15 to 45 years with mean age 28.9 SD±8.8 The presenting features were lumbar pain with on and off fever in 60(60%) cases, dysuria in 15(15%), and in 35(35%) cases was asymptomatic. The renal infection detected in ultrasound bilaterally in 30(30%), Right sided in 35(35%), left sided in 25(25%) and chronic pyelonephritis (change of small size kidney with increase echogenicity and small size kidney with irregular border) in 10(10%) cases. culture and sensitivity seen positive in 27(27%) cases. Pyuria and haematuria seen in 17(17%). The commonest micro-organism detected E.coli in 60(60%), Klebsiella 15(15%), Proteus 5(5%),Enterococcus 5(5%), staphylococcus saprophyticus 5(5%), streptococcus 7(7%), Pseudomonas 3(3%) and insignificant mixed bacterial growth seen in 7 cases. Drug senstivity seen in 100% with meronam, pipracilllin/tazobactam, aztreonam. Nitrofurantoin and amikacin 90% Amoxi-clavulanic acid in fusidic acid, ceftrixone, cotirmoxazole, ofloxin, cefuroxime, cefixime 75% and resistance pattern seen more in ceftazidime, gentamycin, ciprofloxacin and ampcillin. Conclusion: Renal infection detected on ultrasound even with insignificant pyuria and haematuria should not be neglected because having significant positive culture and sensitivity report findings.